Effectiveness of Integrated Traffic Management of Military Police and Traffic Police in Reducing Drive Speed n Arterial Roads: An Experimental Study - Patriot, Teguh (CSID Journal of Infrastructure Development, 2023)
The Indonesian National Police Traffic Corps (KORLANTAS POLRI) and the Army Staff and Command School (SESKOAD) conducted a joint study in early March 2023 to reduce the number of traffic accident victims by implementing traffic regulations by the Military Police and Traffic Police. One of the methods used by KORLANTAS POLRI is the installation of ETLE speed cameras on Jakarta toll roads, such as Cikampek, Jagorawi, Bitung, and others. At the end of 2022, 75 additional speed cameras had been installed on arterial roads in Jakarta. The purpose of this study is to analyze the effectiveness of traffic regulations by the Military Police and Traffic Police in reducing vehicle speed on the road. Data was collected by comparing vehicle speeds before, during, and after passing through the control zone. Data analysis was conducted using N Gain Score and normal distribution statistical tests with a 5% error rate. The study's results showed that the slowdown in vehicle speed through traffic regulation by the Military Police and Traffic Police could reduce speed by 43.76%. More than 95% of road users comply with speed limits when passing through the control zone. Thus, it can be concluded that the implementation of traffic regulations by the Military Police and Traffic Police has met the planning objectives in reducing the number of traffic accident victims. This method has proven effective in reducing vehicle speed and increasing road user awareness of the importance of complying with speed limits. In addition to the installation of speed cameras, traffic regulation carried out by Military Police and Traffic Police officers can be an effective alternative in reducing the number of traffic accidents on the road. This study shows that the collaboration between KORLANTAS POLRI and SESKOAD can provide important insights into traffic safety issues in Indonesia. The implementation of traffic regulations by Military Police and Traffic Police officers can reduce traffic accidents and save lives. The use of modern technology, such as speed cameras, also plays an important role in this effort. It is recommended that this study's findings be shared with other law enforcement agencies to promote greater cooperation in improving traffic safety nationwide. Additionally, public education campaigns should be conducted to raise awareness among road users about the importance of adhering to traffic rules and regulations.